Aberrant NK cell phenotype in a patient with CD25 deficiency - Caldirola, María Soledad (2017)
Human IL-2 receptor α chain deficiency (CD25 deficiency), caused by mutation in the IL2RA gene, is a combined immunodeficiency characterized by invasive viral and bacterial sinopulmonary infections, as well as lymphoproliferation and severe multi organ autoimmune disorders.